PENGARUH DISIPLIN DAN KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMA HKBP TARUTUNG - Nuraini Lumbantobing; Iwan Setiawan Tarigan; Elsina Sihombing (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The objectives of this study include: 1) to determine whether there is a partial influence of the principal's discipline on teacher performance at SMA HKBP 1 and HKBP 2 Tarutung; 2) to determine whether there is a partial influence of the principal's interpersonal communication on teacher performance at SMA HKBP 1 and HKBP 2 Tarutung; and 3) to determine whether there is a simultaneous influence of the principal's discipline and interpersonal communication on teacher performance at SMA HKBP 1 and HKBP 2 Tarutung. The method used in this study is a quantitative research method. The population is all teachers at SMA HKBP 1 and HKBP 2 Tarutung, each 27 and 23 people. The instrument trial was conducted on 20 teachers outside the research sample so that it was known that all research instruments were declared valid and reliable because they had met the validity and reliability value criteria. Data were collected with a closed questionnaire of 95 items. The results of the data analysis show that: 1) the Fcount value > Ftable (k; n-2) (2; 48) is 26.284 > 3.15, thus it is known that there is a positive and significant influence of the principal's discipline on teacher performance at SMA HKBP 1 and HKBP 2 Tarutung. The influence is 35.4%, 2) the Fcount value > Ftable (k; n-2) (2; 48) is 23.725 > 3.15, thus it is known that there is a positive and significant influence of the principal's interpersonal communication on teacher performance at SMA HKBP 1 and HKBP 2 Tarutung. The influence is 33.1%, and 3) the Fcount value > Ftable (k; n-2) (2; 48) is 16.728 > 3.15, thus it is known that there is a positive and significant influence of the principal's discipline and interpersonal communication on teacher performance at SMA HKBP 1 and HKBP 2 Tarutung. The influence is 41.6%, thus Ha is accepted and H0 is rejected